Triadic convergence of Iman, Islam, and Ihsan for building an ethical digital society in the era of Artificial Intelligence - Samsuriyanto Samsuriyanto; Andina Firmandari Imani (PT Bina Perfidia Akademia, 2026)
The rapid development of Artificial Intelligence (AI) has increased the complexity of digital communication, yet existing studies predominantly emphasize technological governance rather than strengthening human spiritual agency as the primary controller of human–AI interaction. This study aims to formulate a Triadic Convergence model integrating the dimensions of Iman, Islam, and Ihsan to construct the characteristics of the Digital Insan Kamil as the controller of digital society. This study employed a qualitative library research approach using conceptual analysis of Islamic theology, digital communication, and Artificial Intelligence literature through an interactive analytical model. The findings demonstrate that Iman functions as an epistemological foundation through Tabayyun, Islam provides normative guidance based on Maqasid al-Shariah, and Ihsan establishes an ethical foundation through Muraqabah. The integration of these three dimensions produces the Digital Insan Kamil model, positioning humans as moral agents who direct AI utilization. This model enriches communication theology studies while offering a new paradigm for developing an ethical digital society. Abstrak Perkembangan Artificial Intelligence (AI) telah meningkatkan kompleksitas komunikasi digital. Namun, kajian yang ada masih lebih berfokus pada regulasi teknologi daripada penguatan agensi spiritual manusia sebagai pengendali utama dalam interaksi manusia–AI. Penelitian ini bertujuan merumuskan model Triadic Convergence yang mengintegrasikan dimensi Iman, Islam, dan Ihsan untuk membangun karakteristik Digital Insan Kamil sebagai pengendali masyarakat digital. Penelitian ini menggunakan pendekatan kualitatif dengan desain library research melalui analisis konseptual terhadap literatur mengenai teologi Islam, komunikasi digital, dan Artificial Intelligence menggunakan model analisis interaktif. Hasil penelitian menunjukkan bahwa dimensi Iman berfungsi sebagai landasan epistemologis melalui Tabayyun, dimensi Islam memberikan pedoman normatif berdasarkan Maqasid al-Shariah, sedangkan dimensi Ihsan membangun fondasi etika melalui Muraqabah. Integrasi ketiga dimensi tersebut menghasilkan model Digital Insan Kamil yang menempatkan manusia sebagai subjek moral dalam mengarahkan pemanfaatan AI. Model ini memperkaya kajian teologi komunikasi sekaligus menawarkan paradigma baru bagi pengembangan masyarakat digital yang beretika.